Increasing Obesity in Treated Female HIV Patients from Sub-Saharan Africa: Potential Causes and Possible Targets for Intervention - McCormick, Claire L.; Francis, Arianne M.; Iliffe, Kim; Webb, Helen; Douch, Catherine J.; Pakianathan, Mark; Macallan, Derek C. (Frontiers in Immunology, 2014)
Objectives To investigate changing nutritional demographics of treated HIV-1-infected patients and explore causes of obesity, particularly in women of African origin. Methods We prospectively reviewed nutritional demographics of clinic attenders at an urban European HIV clinic during four one-month periods at 3-yearly intervals (2001, 2004, 2007, and 2010) and in two consecutive whole-year reviews (2010-11 and 2011-12). Risk-factors for obesity were assessed by multiple linear regression. A sub-study of 50 HIV-positive African female patients investigated body-size/shape perception using numerical, verbal and pictorial cues. Results We found a dramatic rise in the prevalence of obesity (BMI >30 kg/m2), from 8.5% (2001) to 28% (2011-12) for all clinic attenders, of whom 86% were on antiretroviral treatment. Women of African origin were most affected, 49% being obese, with a further 32% overweight (BMI 25-30 kg/m2), in 2012. Clinical factors strongly associated with obesity included female gender, black African ethnicity, non-smoking, age and CD4 count (all P<0.001); greater duration of cART did not predict obesity. Individual weight-time trends mostly showed slow long-term progressive weight gain. Investigating body weight perception, we found that weight and adiposity were underestimated by obese subjects, who showed a greater disparity between perceived and actual adiposity (P<0.001). Obese subjects targeted more obese target “ideal” body shapes (P<0.01), but were less satisfied with their body shape overall (P=0.02). Conclusions Seropositive African women on antiretroviral treatment are at heightened risk of obesity. Although multifactorial, bodyweight perception represents a potential target for intervention.